Analisis Produksi Dan Pendapatan Usahatani Padi Sawah Metode System Of Rice Intensification Di Kecamatan Sindue Kabupaten Donggala - Astuti Astuti (Universitas Tadulako, 2017)
This research aimed at finding out the influence of factors in line with land area factor, seed, Urea fertilizer, Phonska fertilizer, Seprit fertilizer and labours toward the production of rice field cultivated with System of Rice Intensification (SRI) method at Lero Tataro Village, Sindue district, Donggala regency. The 40 respondents were taken through census method. A multiple linier regression was used to analyze the data. The results showed that the independent variable (Xi) gave a big influence toward the dependent variable (Y). The coefficient of determination (R2) was 0.979 which means that 98 percent of the variations of rice field’s production can be explained by the variable of land area (X1), seed (X2), Urea fertilizer (X3), Phonska fertilizer (X4), Seprit fertilizer (X5), and the labour (X6). The other 2 percent was explained out of the model. It can be said that farm production through System of Rice Intensification (SRI) method at Lero Tatari village were obviously influenced by the land area, seed, Urea fertilizer, Phonska fertilizer, Seprit fertilizer, and labours. The income of farm production using System of Rice Intensification (SRI) Method at Lero Tatari, Sindue district was Rp. 13.023.005.88/0.76 ha, or Rp. 17.079.351.97/ha.